CHILDREN'S FOLKLORE AND MUSICAL PRACTICES: CULTURAL AND EDUCATIONAL VALUE IN THE CONTEXT OF APPLIES ETHNOMUSICOLOGY (Heritage, 2025)
Musical folklore constitutes a crucial component of intangible cultural heritage and functions as a potent pedagogical medium within the context of early childhood education. This study investigates the educational potential of traditional children’s songs, counting rhymes, and music-based games in preschool environments, with particular emphasis on their contribution to the development of cultural identity, language acquisition, rhythmic awareness, motor coordination, and socio-emotional competencies. Drawing upon a curated corpus of 343 folklore units sourced from educational and ethnomusicological literature published between 1928 and 2022, the research undertakes a genre-specific and functional taxonomy of the most prevalent forms. These encompass counting-out rhymes, movement-based songs, patterned songs, lullabies, and ritual songs.            The findings indicate that the most recurrent forms—particularly counting rhymes and songs involving physical activity—offer multifaceted developmental advantages. These include the facilitation of articulation, enhancement of phonological awareness, promotion of group cohesion, and reinforcement of a sense of cultural belonging. Special attention is given to the pedagogical significance of the "mother tongue melody"—musical structures that reflect the phonetic and rhythmic characteristics of the native language—as a key factor in early speech development and emotional attachment.            The study underscores the collaborative role of both families and educators in the preservation and intergenerational transmission of musical folklore, asserting that traditional songs and games transcend mere entertainment to serve as culturally and educationally substantive practices. The integration of folklore into preschool curricula is thus advocated as a means of providing authentic cultural experiences that support identity formation and holistic child development.            Situated within an interdisciplinary framework that draws from ethnomusicology, pedagogy, and cultural studies, this research argues that the systematic incorporation of musical folklore into early childhood education is not only pedagogically advantageous, but essential for fostering cultural continuity and cultivating national consciousness among emerging generations.
Keywords: musical folklore, intangible cultural heritage, еducational function, preschool education; culutral identity